2022
DOI: 10.1038/s41420-022-00968-9
|View full text |Cite
|
Sign up to set email alerts
|

A positive feedback loop: RAD18-YAP-TGF-β between triple-negative breast cancer and macrophages regulates cancer stemness and progression

Abstract: As a key regulator of the DNA translesion synthesis (TLS) pathway, RAD18 is error-prone and contributes to the accumulation of DNA mutations. Our previous study showed that it plays an essential role in the progression of multiple tumors. However, the mechanism through which RAD18 influences triple-negative breast cancer (TNBC), especially the interaction between tumor cells and the tumor microenvironment, remains elusive. In this study, we showed that RAD18 expression is markedly higher in patients with high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Our results displayed a connection between the nuclear YAP and the upregulation of TGF‐β1, which were in correspondence with previously published studies that knocked out of LATS1/2 could lead to decreased expression of phosphorylated YAP, which could cause increased expression of TGF‐β in mouse neuroepithelium and liver cells 49,50 . Other studies also showed that when the activity of YAP was inhibited with Verteporfin, the TGF‐β pathway was hindered in fibroblast, 51 and the secretion of TGF‐β by macrophages was diminished 52 . These results suggest a possible crosstalk between Hippo and TGF‐β pathways where dephosphorylated YAP could translocate into the nucleus to activate the TGF‐β signaling pathway.…”
Section: Discussionsupporting
confidence: 88%
“…Our results displayed a connection between the nuclear YAP and the upregulation of TGF‐β1, which were in correspondence with previously published studies that knocked out of LATS1/2 could lead to decreased expression of phosphorylated YAP, which could cause increased expression of TGF‐β in mouse neuroepithelium and liver cells 49,50 . Other studies also showed that when the activity of YAP was inhibited with Verteporfin, the TGF‐β pathway was hindered in fibroblast, 51 and the secretion of TGF‐β by macrophages was diminished 52 . These results suggest a possible crosstalk between Hippo and TGF‐β pathways where dephosphorylated YAP could translocate into the nucleus to activate the TGF‐β signaling pathway.…”
Section: Discussionsupporting
confidence: 88%
“…JH-RE-06 also suppresses growth of A549 and H1299 lung cancer cells grown as xenografts in vivo ( 155 ). Further consistent with a role for TLS in sustaining tumors, RAD18 overexpression elevates colonization of esophageal cancer cells in the mice lung ( 156 ), while RAD18-deficient TNBC xenografts show reduced tumor volume ( 157 ). Taken together, these studies suggest that TLS is a cancer-dependency at least under select conditions.…”
Section: Evidence That Tls Polymerases Contribute To Cancermentioning
confidence: 59%
“…Implanting cancer cells orthotopically in mice provides a convenient approach to study tumor growth in a physiologically relevant environment. Orthotopic injection of esophageal cancer cells overexpressing RAD18 increases colonization ( 156 ), while RAD18-deficient TNBC cell xenografts show reduced tumor growth ( 157 ). TLS inhibition by the REV1 inhibitor JH-RE-06 decreases colonization of lung cancer cells in mice ( 155 ).…”
Section: Evidence That Tls Polymerases Contribute To Cancermentioning
confidence: 99%
“…Moreover, BA dose-dependently inhibited the GRP78-mediated secretion of TGF-β, thereby suppressing macrophage polarization, IL-6 secretion, and IL-6-mediated gastric cancer stemness ( Figure 6 ). In a previous study, TGF-β signaling was reported to involve a positive feedback loop in the regulation of triple-negative breast cancer and macrophage-mediated cancer stemness and progression [ 41 ]. The results also indicated that BA-induced downregulation of TGF-β through the GRP78-mediated pathway may inhibit the positive feedback loop between gastric cancer cells and macrophage-mediated cancer stemness and tumor progression.…”
Section: Discussionmentioning
confidence: 99%